Atherogenic dyslipidemia, but not hyperglycemia, is an independent factor associated with liver fibrosis in subjects with type 2 diabetes and NAFLD: a population-based study. Issue 4 (April 2021) - Julián, María Teresa; Pera, Guillem; Soldevila, Berta; Caballería, Llorenç; Julve, Josep; Puig-Jové, Carlos; Morillas, Rosa; Torán, Pere; Expósito, Carmen; Puig-Domingo, Manel; Castelblanco, Esmeralda; Franch-Nadal, Josep; et al.
Abstract : Objective: To investigate the prevalence and risks factors associated with the presence of liver fibrosis in subjects with nonalcoholic fatty liver disease (NAFLD) with and without type 2 diabetes mellitus (T2D). Design and methods: This study was part of a population-based study conducted in the Barcelona metropolitan area among subjects aged 18–75 years old. Secondary causes of steatosis were excluded. Moderate-to-advanced liver fibrosis was defined as a liver stiffness measurement (LSM) ≥ 8.0 kPa assessed by transient elastography. Results: Among 930 subjects with NAFLD, the prevalence of moderate-to-advanced liver fibrosis was higher in subjects with T2D compared those without (30.8% vs 8.7%). By multivariable analysis, one of the main factors independently associated with increased LSM in subjects with NAFLD was atherogenic dyslipidemia but only in those with T2D. The percentage of subjects with LSM ≥ 8.0 kPa was higher in subjects with T2D and atherogenic dyslipidemia than in those with T2D without atherogenic dyslipidemia both for the cut-off point of LSM ≥8.0 kPa (45% vs 24% P  = 0.002) and ≥13 kPa (13% vs 4% P  = 0.020). No differences were observed in the prevalence of LSM ≥8.0 kPa regarding glycemic control among NAFLD-diabetic subjects. Conclusions: Factors associated with moderate-to-advanced liver fibrosis in NAFLD are different in subjects with and without T2D. Atherogenic dyslipidemia was associated with the presence of moderate-to-advanced liver fibrosis in T2D with NAFLD but not in non-diabetic subjects. These findings highlight the need for an active search for liver fibrosis in subjects with T2D NAFLD and atherogenic dyslipidemia.